2011
DOI: 10.1007/s12664-011-0129-1
|View full text |Cite
|
Sign up to set email alerts
|

Pulmonary manifestations in inflammatory bowel disease: a prospective study

Abstract: PFT and HRCT chest showed abnormality in about one-quarter of patients with IBD. A majority of patients with these abnormalities were asymptomatic.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
31
0
6

Year Published

2016
2016
2019
2019

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 51 publications
(41 citation statements)
references
References 15 publications
2
31
0
6
Order By: Relevance
“…also found PFT abnormalities, obstructive pattern, abnormal DLCO, and restrictive pattern in 53%, 22.7%, 28.8%, and 1.5%, of patients with UC, respectively. In an Indian study of 27 of 95 (28.5%) patients with inflammatory bowel disease (83 UC and 12 Crohn's disease), small airway obstruction was seen in 18, restrictive defect in 6, and mixed defect in 3 patients 31. Our results are somewhat in accordance with that study 31…”
Section: Discussionsupporting
confidence: 90%
“…also found PFT abnormalities, obstructive pattern, abnormal DLCO, and restrictive pattern in 53%, 22.7%, 28.8%, and 1.5%, of patients with UC, respectively. In an Indian study of 27 of 95 (28.5%) patients with inflammatory bowel disease (83 UC and 12 Crohn's disease), small airway obstruction was seen in 18, restrictive defect in 6, and mixed defect in 3 patients 31. Our results are somewhat in accordance with that study 31…”
Section: Discussionsupporting
confidence: 90%
“…Patients with CD were 1.4-3.0 times more likely to report respiratory symptoms than patients with UC. Other studies showed that respiratory symptoms were reported by 26-48% of IBD patients, which was more frequent than in healthy people [23][24][25][26][27].…”
Section: Epidemiologymentioning
confidence: 91%
“…Up to 58% of these patients had at least one abnormal value in PFT [23][24][25][26][27][28]. Impairment of diffusion lung capacity for carbon monoxide (DLCO) was most commonly found [23][24][25][26][27][28].…”
Section: Epidemiologymentioning
confidence: 99%
See 2 more Smart Citations